Names to denote smells in proto-Slavic language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
Study of the history of lexical structure of Ukrainian language is impossible without finding out the history of some semantic groups. The analysis of the thematic groups with odoratissima roots (etymological dictionary) represents the vocabulary of odor in the proto-Slavic period.
Keywords: smell odorativnaya vocabulary; derivatives; root; token; derivative